Detection of tsunami‐driven phase and amplitude perturbations of subionospheric VLF signals following the 2010 Chile earthquake. Issue 6 (16th June 2014) - Rozhnoi, A.; Shalimov, S.; Solovieva, M.; Levin, B.; Shevchenko, G.; Hayakawa, M.; Hobara, Y.; Walker, S. N.; Fedun, V.
Abstract We report on specific fluctuations in phase and amplitude of VLF signals that correlate both spatially and temporally with the passage of the tsunamis recorded by the Deep‐ocean Assessments and Reporting of Tsunamis bottom pressure stations. Measurements from the VLF/LF receiver sited in Petropavlovsk‐Kamchatsky and sensor buoys placed throughout the Pacific Ocean at great distances (Hawaii and Japan) from the epicenter are consistent with the hypothesis that the ocean tsunami following the Chile earthquake on 27 February 2010 radiated internal gravity waves which propagated through the lower ionosphere.